Analysis Of Subsidized Fuel Policy As An Instrument Of Indonesia’s Economic Stability Amid Global Energy Price Volatility - Muhamad Ardi Goltom (Jurnal Ilmiah Ekonomi Global Masa Kini, 2026)
This study analyzes the subsidized fuel (BBM Bersubsidi) policy as an instrument for Indonesia's economic stability amid fluctuations in global energy prices. A surge in world energy prices indirectly impacts the rise of commodity prices, increases production costs—specifically driven by higher transportation expenses—and inflates the fiscal burden on the State Budget (APBN). The government plays a crucial role in market intervention to prevent these external shocks from destructively transmitting into the domestic economy. This study aims to analyze the effectiveness of the government's policy role in maintaining macroeconomic stability amidst a global energy crisis. The method employed is a descriptive qualitative approach through a literature review, examining various scientific literatures, secondary data, and relevant policies. The results demonstrate that the mix of fiscal policy, monetary policy, and energy governance for subsidized commodities is proven effective in curbing inflation and maintaining economic stability in the short term. However, its long-term effectiveness heavily relies on the resilience of the state budget (APBN) burden. The implications of this study emphasize the necessity of other complementary policies as a follow-up to optimize the subsidized fuel policy, which will impact the economic balance from the short to the long term. These include maintaining national economic stability and growth, creating a favorable investment environment (encompassing the preservation of purchasing power, along with integrated infrastructure), and maintaining public trust and stability toward the Rupiah.Keywords: Economic Stability, Energy Crisis, Fiscal Policy, Monetary Policy.